Olfactory neurogenesis and its role in fear memory modulation - Silvas-Baltazar, Monserrat; López-Oropeza, Grecia; Durán, Pilar; Martínez-Canabal, Alonso (Frontiers in Behavioral Neuroscience, 2023)
Olfaction is a critical sense that allows animals to navigate and understand their environment.In mammals, the critical brain structure to receive and process olfactory information is the olfactory bulb, a structure characterized by a laminated pattern with different types of neurons, some of which project to distant telencephalic structures, like the piriform cortex, the amygdala, and the hippocampal formation. Therefore, the olfactory bulb is the first structure of a complex cognitive network that relates olfaction to different types of memory, including episodic memories. The olfactory bulb continuously adds inhibitory newborn neurons throughout life; these cells locate both in the granule and glomerular layers and integrate into the olfactory circuits, inhibiting projection neurons. However, the roles of these cells modulating olfactory memories are unclear, particularly their role in fear memories. We consider that olfactory neurogenesis might modulate olfactory fear memories by a plastic process occurring in the olfactory bulb.